2014
DOI: 10.1097/01.sa.0000446363.59891.8a
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial Anesthesia Decreases Postoperative Systemic Infection Risk Compared With General Anesthesia in Knee Arthroplasty

Abstract: Background-Surgical stress has been previously shown to result in immune disturbance. Neuraxial anesthesia (NA) has been long hypothesized to blunt undesired surgical insults, and thus limit immune compromise and improve surgical outcomes. We hypothesized that neuraxial anesthesia would decrease postoperative infectious complications compared to general anesthesia among knee arthroplasty patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Preventive measures such as timely administration of antibiotics, maintenance of normothermia, and minimizing transfusions are well known 28 , but previous reports did not show regional anesthesia to have as important an effect on deep surgical site infections after total hip or knee replacement 29,30 . Possible mechanisms for how regional anesthesia lowers the prevalence of deep surgical site infection might be alterations in immune response 31 and sympathetic blocking effects with concomitant vasodilation improving tissue perfusion and oxygenation 32 .…”
mentioning
confidence: 99%
“…Preventive measures such as timely administration of antibiotics, maintenance of normothermia, and minimizing transfusions are well known 28 , but previous reports did not show regional anesthesia to have as important an effect on deep surgical site infections after total hip or knee replacement 29,30 . Possible mechanisms for how regional anesthesia lowers the prevalence of deep surgical site infection might be alterations in immune response 31 and sympathetic blocking effects with concomitant vasodilation improving tissue perfusion and oxygenation 32 .…”
mentioning
confidence: 99%
“…We not only examined the incidence of CNS infection after administration of neuraxial anesthesia, but also compared general and neuraxial anesthesia in this special population to determine whether neuraxial anesthesia is associated with a lower risk of systemic infections. The effect of neuraxial anesthesia on the rate of postoperative infections, particularly surgical site infections, is contradictory [6,7,18]. Liu et al [18] and Chang et al [6], using two large databases respectively, found that neuraxial anesthesia was associated with lower risks of systemic and surgical site infections compared with general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of neuraxial anesthesia on the rate of postoperative infections, particularly surgical site infections, is contradictory [6,7,18]. Liu et al [18] and Chang et al [6], using two large databases respectively, found that neuraxial anesthesia was associated with lower risks of systemic and surgical site infections compared with general anesthesia. Neuraxial anesthesia may decrease the risk of a surgical site infection via transfusion, which has been shown to be a risk factor for surgical site infections [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study [1] of 16,555 patients suggested that neuraxial anesthesia is associated with lower odds of infectious complications comparing to general anesthesia. To test the effect of type of anesthesia on our regression model, we conducted further regression analysis with the type of anesthesia as an independent variable.…”
mentioning
confidence: 95%
“…Finally, blood transfusion is recorded in the NSQIP database, and was included in our previous analysis [1]. Although blood transfusion is not a benign risk factor, the study of its effect is not a simple task especially considering the heterogeneous practice protocols across more than 400 institutions as included in the NSQIP database.…”
mentioning
confidence: 99%